Privacidade e proteção de dados: interpretação e alcance das hipóteses legais de tratamento dos dados pessoais na Lei Geral de Proteção de Dados Pessoais (LGPD) – Lei nº 13.709/2018 - Thomaz, Alan Campos Elias (2022)
This paper aims to analyze the interpretation and extension of the legal grounds that allow the processing of personal data, based on the Brazilian General Data Protection Law (LGPD) – Law n. 13.709/18. According to the LGPD, each personal data processing activity must be justified on a lawful basis. Thus, it is crucial to understand the extent of using the lawful bases in articles 7th and 11 of the law. In the absence of regulation of the extension of the bases by the National Data Protection Authority, the correct understanding it aims to provide legal certainty to organizations subject to LGPD, which need to choose the best legal hypothesis to justify the processing of personal data in the context of their business activities. In addition, this research analyzes whether there is a preference or hierarchy between the legal hypothesis of consent and the other legal hypotheses provided for in the LGPD, and also analyze two data protection microsystems provided for in the LGPD, the processing of publicly accessible data and data regarding children and teenagers. Finally, this work analyzes specific characteristics of the choice of the lawful basis, including how to document it, when such a choice should be made, and whether the legal base can be changed later. Brazilian doctrine, foreign doctrine, and guidelines from data protection authorities on the European General Data Protection Regulation are observed to conduct this analysis.